A conversão das almas do Oriente : franciscanos, poder e catolicismo em Goa : séculos XVI e XVII - Faria, Patricia Souza de (2008)
The main of that study consist in analyzing the conversion process of Indian people to Catholicism focused in XVI and XVII centuries detaching the actuation of Franciscan Order and considering the Franciscan Reform context of Observance. We are trying to identify the strategies that make more useful by Franciscans in Goa's citizens conversions to Catholicism and we are showing this process considering faith an Indians sorts. We have just thinking about to understand the facts by Catholic Missionaries view and what they do about and their ideas in the process that have been happened. Our understanding reflects about the difficulties of social insertion that are faced by native clergymen (who was descent from Portuguese in India or who are descent from the sort of Brahmans or Kshatryas). We are detaching the rivalries among born Portugal reign Christians, Indian born Christians and the loggerheads among different sort members. The texts wrote by the Indian Christian's born will be focused. The "instrument of social discipline" concept (used by authors like Elias, Weber, Foucault, Palomo, Prosperi) was adopted to analyse the conversion process to Catholicism in India and its people. The Concilii, The Saint Office Tribunal of Goa and the Episcopal and Parochial community have an elucidative place in our thesis.